Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3847/1538-4357/aadfd6
|View full text |Cite
|
Sign up to set email alerts
|

The White Dwarf Initial–Final Mass Relation for Progenitor Stars from 0.85 to 7.5 M

Abstract: We present the initial-final mass relation (IFMR) based on the self-consistent analysis of Sirius B and 79 white dwarfs from 13 star clusters. We have also acquired additional signal on eight white dwarfs previously analyzed in the NGC 2099 cluster field, four of which are consistent with membership. These reobserved white dwarfs have masses ranging from 0.72 to 0.97 M ⊙ , with initial masses from 3.0 to 3.65 M ⊙ , where the IFMR has an important change in slope that these new data help to observationally conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
369
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(411 citation statements)
references
References 86 publications
21
369
1
Order By: Relevance
“…Obtained system parameters allowed us to make some assumptions about the past and future of the GPX-TF16E-48. Based on the current mass of the WD and the semiempirical MIST model of initial-final mass relation of WDs from Cummings et al 2018, the progenitor mass was close to 2.9 M . After the main sequence stage, the primary evolved into a red giant forming a common envelope and then into a cooling white dwarf.…”
Section: Discussionmentioning
confidence: 94%
“…Obtained system parameters allowed us to make some assumptions about the past and future of the GPX-TF16E-48. Based on the current mass of the WD and the semiempirical MIST model of initial-final mass relation of WDs from Cummings et al 2018, the progenitor mass was close to 2.9 M . After the main sequence stage, the primary evolved into a red giant forming a common envelope and then into a cooling white dwarf.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, when convection is included both at the CE and at the PDCZ, the final masses predicted by stellar evolution sequences fall well below the range indicated by semiempirical IFMR (Cummings et al 2018;El-Badry et al 2018). This suggests that either the TP-AGB is too short or that third dredge-up is too strong, inhibiting the growth of the H-free core during the TP-AGB.…”
Section: Tension Between Different Observational Constraintsmentioning
confidence: 91%
“…However, it has also been shown that the inclusion of the value for f CBM as calibrated by upper main sequence stars at all convective boundaries (e.g. in Weiss & Ferguson 2009) results in such efficient third dredge-up that core growth is suppressed during the TP-AGB, leading to an IFMR that is in tension with observations, the predicted final mass being too low by ∼ 0.1...0.2M for initial masses in the range ∼ 2...4M (Salaris et al 2009;Cummings et al 2018;El-Badry et al 2018). CBM below the convective envelope (CE) plays two different roles.…”
Section: Convective Envelope and Pulse-driven Convective Zonementioning
confidence: 97%
See 2 more Smart Citations